1987
DOI: 10.1007/bf00444956
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal limb gangrene and renal vein thrombosis

Abstract: A 3-day-old male infant born to a non-diabetic mother was admitted to the University Hospital with gangrene of the right forearm and some gangrenous patches of the left forearm. This was associated with left renal vein thrombosis. Screening tests for coagulation disorders gave normal results. The gangrenous right forearm was amputated and subsequently grafted. The skin lesions of the left forearm were successfully grafted. The renal system recovered well on supportive measures. The course of hospitalization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, expectant management still has its success in selected cases [12, 51]. However, early diagnosis and prompt management are the essential parts for preserving limb function and perfusion as some cases were associated with a favorable outcome [3, 20, 22, 26]. There are no large trials comparing different therapeutic regimens [7, 52], making the decision highly individualized and based on clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expectant management still has its success in selected cases [12, 51]. However, early diagnosis and prompt management are the essential parts for preserving limb function and perfusion as some cases were associated with a favorable outcome [3, 20, 22, 26]. There are no large trials comparing different therapeutic regimens [7, 52], making the decision highly individualized and based on clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolism to the brachial artery before delivery was felt to be the cause of the gangrene [32]. Nazer et al have reported on brachial artery thrombosis as a result of paradoxical embolism from the renal vein passing through a patent foramen ovale [23].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation varies depending on the extremity involved and the initial timing of thrombosis [1,2]. Several case reports on extremity hypoperfusion and gangrene due to intrauterine thrombosis at birth can be found in the literature [1,2,3,4,5,6,7,8,9,10]. Although the condition is usually associated with a poor prognosis, favorable outcomes have also been reported [3,4] (table 1).…”
Section: Introductionmentioning
confidence: 99%